Israelenses e Palestinos: a questão da identidade no documentário Nosotros, ellos e yo (2015), de Nicolás Avruj - Lodos, Claudinei [UNIFESP] (2020)
The documentary NEY: Nosotros, Ellos y Yo (2015), directed by Nicolás Avruj, depicts the conflict between Israelis and Palestinians from the standpoint of an Argentinian Jew in crisis with his identity. In 2000, during the second Intifada, the director travelled to the Middle East, filming the area and interviewing both Israelis and Palestinians. The trip concerns for a deep look into traditions and knowledge of both peoples, whose histories do not refer to Arabian or Jewish culture only, but mainly to long-standing political confronts. The Argentinian documentary is autobiographic and came out of the travel experience and of an editing process that took fifteen years to be launched. The issue about the Jewish identity pervades the movie and can be understood from the director trip and the period of time in which he remained producing the film. NEY’s subjectivity is highlighted by the conflict representation between Israel and Palestine made through the fact reminiscence which took place in 2000 during the director’s journey. The dyad “we” and “they”, emphasizeThe documentary NEY: Nosotros, Ellos y Yo (2015), directed by Nicolás Avruj, depicts the conflict between Israelis and Palestinians from the standpoint of an Argentinian Jew in crisis with his identity. In 2000, during the second Intifada, the director travelled to the Middle East, filming the area and interviewing both Israelis and Palestinians. The trip concerns for a deep look into traditions and knowledge of both peoples, whose histories do not refer to Arabian or Jewish culture only, but mainly to long-standing political confronts. The Argentinian documentary is autobiographic and came out of the travel experience and of an editing process that took fifteen years to be launched. The issue about the Jewish identity pervades the movie and can be understood from the director trip and the period of time in which he remained producing the film. NEY’s subjectivity is highlighted by the conflict representation between Israel and Palestine made through the fact reminiscence which took place in 2000 during the director’s journey. The dyad “we” and “they”, emphasized on the documentary title, represents groups that are opposed, distant and asymmetrical. The “multiple identities” are made clear in the group represented by “we” (Argentinians) and “the” (Israelis and Palestinians). The aim of this essay is to realize in which ways the documentary represents the director’s identity crisis and the conflict in the area, considering the historicity of this war which has been lasting for over a century.d on the documentary title, represents groups that are opposed, distant and asymmetrical. The “multiple identities” are made clear in the group represented by “we” (Argentinians) and “the” (Israelis and Palestinians). The aim of this essay is to realize in which ways the documentary represents the director’s identity crisis and the conflict in the area, considering the historicity of this war which has been lasting for over a century.